2011
DOI: 10.1105/tpc.111.091033
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a SAL1-PAP Chloroplast Retrograde Pathway That Functions in Drought and High Light Signaling in Arabidopsis      

Abstract: Compartmentation of the eukaryotic cell requires a complex set of subcellular messages, including multiple retrograde signals from the chloroplast and mitochondria to the nucleus, to regulate gene expression. Here, we propose that one such signal is a phosphonucleotide (39-phosphoadenosine 59-phosphate [PAP]), which accumulates in Arabidopsis thaliana in response to drought and high light (HL) stress and that the enzyme SAL1 regulates its levels by dephosphorylating PAP to AMP. SAL1 accumulates in chloroplasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
578
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 478 publications
(598 citation statements)
references
References 82 publications
19
578
1
Order By: Relevance
“…The 59-phosphoadenosine 39-phosphate (PAP) formed from PAPS after transfer of the sulfate group is a potent inhibitor of sulfotransferases and RNases, and its accumulation leads to large changes in gene expression, metabolite accumulation, plant morphology, and stress resistance (Estavillo et al, 2011;Lee et al, 2012). PAP is degraded to AMP and Pi by the phosphatase FIERY/Increased Salt Tolerance (FRY1/SAL1) localized in plastids, indicating again a need for a PAP transporter in plastidic membranes (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The 59-phosphoadenosine 39-phosphate (PAP) formed from PAPS after transfer of the sulfate group is a potent inhibitor of sulfotransferases and RNases, and its accumulation leads to large changes in gene expression, metabolite accumulation, plant morphology, and stress resistance (Estavillo et al, 2011;Lee et al, 2012). PAP is degraded to AMP and Pi by the phosphatase FIERY/Increased Salt Tolerance (FRY1/SAL1) localized in plastids, indicating again a need for a PAP transporter in plastidic membranes (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25] Two new plastid retrograde signals (PAP and MEcPP) during drought, high light and wounding stress responses have been revealed by two research teams, involving the analysis of the Arabidopsis mutants sal1 and ceh1, which encode the plastid nucleotidase/phosphatase SAL1 and hydroxyl-2-methyl-2-(E)-butenyl4-diphosphate synthase (HDS), respectively. 26,29 Analysis of the rps1 mutant demonstrated that the chloroplast ribosomal protein S1 (RPS1) mediates retrograde signaling to modulate the expression of the heat-responsive nuclear transcription factor HsfA2 and its target genes during heat stress, although the specific plastid retrograde signal is unknown. 30 Recently, gene cloning and transcriptional analysis of the Arabidopsis ammonium-overly-sensitive 1 (amos1) that are needed for maintaining the stability of the thylakoid membrane system under normal growth conditions.…”
Section: Molecular Components In Plastid Retrograde Signaling To Regumentioning
confidence: 99%
“…An example of the first type can be seen in chloroplastic SAL1, a phosphatase that regulates the level of its substrate 3'-phosphoadenosine-5'-phosphate (PAP); high levels of PAP were demonstrated to accumulate in sal1 mutants. 26 Similarly, the stress-inducible nuclear HDS gene encodes a plastidial enzyme that participates in isoprenoid synthesis, converting methylerythritol cyclodiphosphate (MEcPP) to hydroxymethylbutenyl diphosphate (HMBPP) in the methylerythritol phosphate (MEP) pathway in plastids; large amounts of MEcPP were shown to accumulate in ceh1 mutants. 29 Likewise, tAPX regulates the production of H 2 O 2 in chloroplasts.…”
Section: Interaction Of Plastid Retrograde Signaling and Aba Signalinmentioning
confidence: 99%
See 2 more Smart Citations